Flowering Time Gene Variation in Brassica Species Shows Evolutionary Principles - Schiessl, Sarah V.; Huettel, Bruno; Kuehn, Diana; Reinhardt, Richard; Snowdon, Rod J. (Frontiers in Plant Science, 2017)
Flowering time genes have a strong influence on successful reproduction and life cycle adaptation. However, their regulation is highly complex and only well understood in diploid model systems. For crops with a polyploid background from the genus Brassica, data on flowering time gene variation are scarce, although indispensable for modern breeding techniques like marker-assisted breeding. We have deep-sequenced all paralogs of 35 Arabidopsis thaliana flowering regulators using Sequence Capture followed by Illumina sequencing in two selected accessions of the vegetable species Brassica rapa and Brassica oleracea, respectively. Using these data, we were able to call SNPs, InDels and copy number variations (CNVs) for genes from the total flowering time network including central flowering regulators, but also genes from the vernalisation pathway, the photoperiod pathway, temperature regulation, the circadian clock and the downstream effectors. Comparing the results to a complementary data set from the allotetraploid species Brassica napus, we detected rearrangements in B. napus which probably occurred early after the allopolyploidisation event. Those data are both a valuable resource for flowering time research in those vegetable species, as well as a contribution to speciation genetics.